Toxina botulinica versus laser de baixa potência no tratamento de enxaqueca crônica - Loeb, Luana Mazzacoratti [UNIFESP] (2016)
Chronic migrane (CM) is a neurological disorder affecting 2 to 3% of population being characterized by severe debilitating headache occurring during 15 or more days/month. The control of CM is difficult and requires a multidisciplinary approach. Thus, different receptors/molecules can be targeted during pharmacological preventive treatment, with serious side effects. Thus challenging for alternatives therapies is necessary. The aim of this work was to compare patients with CM treated with botulinum toxin A (BT-A) versus low level laser therapy (LLLT), concerning to: pain days, pain intensity, intake of prophylactic drugs/medication, jitters and sleep disorders, in both treatments. Thus, patients were randomized in two groups: Group BT-A (n=18) and Group LLLT (n=18). Each patient filled three pain diaries, being one before baseline (30 days), one during treatment (30 days) and one after post-treatment phases (30 days). Repeated ANOVA plus Bonferroni post-test, Student T test, factorial analysis were used and p<0.05 was accepted. Our data shows that both treatments were able to reduce pain days, ingestion of drugs and decrease the intensity of pain, during crisis. In addition, nervousness was reduced in BT-A group, while sleep disturbance was reduced in LLLT group. In this context our data showed that both treatments can be used to treat CM, without differences between them. However, BT-A is an invasive and expensive method, while the LLLT is a longer treatment (05 weeks) but it is cheaper. In this context, both therapies can be employed to treat CM in medical practice with similar results.